Children's patience and schooltrack choices several years later: Linking experimental and field data - Silvia Angerer; Jana Bolvashenkova; Daniela Glätzle-Rützler; Philipp Lergetporer; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2021)
We present direct evidence on the link between children's patience and educational-track choices years later. Combining an incentivized patience measure of 493 primary-school children with their high-school track choices taken at least three years later at the end of middle school, we find that patience significantly predicts choosing an academic track. This relationship remains robust after controlling for a rich set of covariates, such as family background, school-class fixed effects, risk preferences, and cognitive abilities, and is not driven by sample attrition. Accounting for middle-school GPA as a potential mediating factor suggests a direct link between patience and educational-track choice.
hdl:21.11116/0000-0008-938D-3
Keywords: C91; D90; I21; J2; 330; patience; education; school track choice; children; lab-in-the-field experiment